1971
DOI: 10.1073/pnas.68.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Folded Genome of Escherichia coli Isolated in a Protein-DNA-RNA Complex

Abstract: The DNA of Escherichia coli has been isolated in a compact structure containing small amounts of protein and RNA and having a sedimentation coefficient of approximately 3200 S. The molecular weight of the DNA in the complex is very large (probably higher than 109); the protein is predominantly core RNA polymerase; the RNA is chiefly nascent messenger and ribosomal chains. Solutions containing the complex have low vicosities; this plus its sedimentation rate suggest that the DNA is in a tightly folded conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
1

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(138 citation statements)
references
References 27 publications
2
135
1
Order By: Relevance
“…The stability of RNA polymerase elongation complexes demonstrated here is not unreasonable in light of the salt resistance of the RNA elongation reaction (31-33) and the co-purification of endogenous RNA polymerase with chromatin (34,35). Not all DNA-protein complexes penetrate into agarose gels.…”
Section: Discussionmentioning
confidence: 95%
“…The stability of RNA polymerase elongation complexes demonstrated here is not unreasonable in light of the salt resistance of the RNA elongation reaction (31-33) and the co-purification of endogenous RNA polymerase with chromatin (34,35). Not all DNA-protein complexes penetrate into agarose gels.…”
Section: Discussionmentioning
confidence: 95%
“…In E. coli, the chromosome consists of 4.7 Mbp of DNA which, when extended, is about 1.5 mm long [3]. The chromosome is packaged into a nucleoid in a cell only 1 μm long and hence mandates a highly ordered structure [4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…A comparison of nucleoids obtained by this lysis procedure with those obtained using the original method of Stonington and Pettijohn (1971) has also been published (Dworsky, 1976), and indicated that membrane could stabilize folded chromosomes at low salt concentrations or after treatment with rifampicin in vivo or RNase in vitro. By combining sedimentation and viscometry, Drlica and Worcel (1975) This seemed to indicate that proteins were involved in stabilization of the folded chromosome.…”
Section: Ultraviolet Radiation Damage and Repairmentioning
confidence: 99%
“…This was first accomplished by Stonington and Pettijohn (1971) who lysed spheroplasts of E. coli with and deoxycholate in 1M NaCl. Neutral sucrose gradient analysis of the lysate revealed that the DNA sedimented as a highly-compact, 3200S structure, whose composition was 80% DNA, 10% RNA, and 10% protein by weight.…”
Section: Ultraviolet Radiation Damage and Repairmentioning
confidence: 99%